Problem Solving Learning in Science Education: A Systematic Literature Review - Endang Susilawati; Ida Hamidah; Nuryani Rustaman; Winny Liliawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to describe the application of problem solving in the learning process and describes the technique of forming groups that are carried out in learning. This study uses the Systematic Literature Review method, which focuses on reviewing and analyzing broadly and thoroughly some of the literature that is relevant to the research topic. The stages carried out in this research are clarification and approach; search, filter, and select;  analysis and interpretation; draft articles; and dissemination. Literature data used as the main source in this study were 15 articles from Scopus-indexed Springer within a period of 6 years (2018-2023). The articles analyzed examined problem solving skills ranging from junior high school to university. The results showed problem solving research was carried out individually and in groups, and most research was done through groups. The technique of forming groups is carried out by paying attention to the background, results of initial ability tests in individual rounds, pretest, and educational strata. The steps taken in learning problem solving are: orientation of students to problems; group formation; carrying out investigative activities to solve problems; discussing and reviewing problem solving strategies in groups; making presentations; and the teacher providing feedback.